Image Steganography Technique by Using MSUSAN Algorithm - Abdulamir A.; Zainab (University of Thi-Qar Journal, 2020)
Nowadays, the protection of secret data, which is being sent during transmission channel, has become one of the most important challenges in the information security. Therefore, the using of multimedia technology to provide data protection is needed. Hence, one of the most common data security methods used is image steganography. This paper applied “Modified Smallest Univalue Segment Assimilating Nucleus” (MSUSAN) algorithm to detect the interest points, which it are used to steganography, so that the embedding process in the area containing the edges or corners is less susceptible to discovery because the human eye is not sensitive to the change of edges. So when the nucleus is a candidate corner, the block detected as a rough block. Whereas the nucleus isn’t a candidate corner, the block detected as smooth block. The least significant bit (“LSB”) technique is used to hide 3 bits in the rough block while 2 bits are hidden in the smooth block. Therefore, this method is of high efficiency in terms of payload rate, “Peak Signal Noise Ratio”(PSNR) and “Mean Square Error”( MSE) which gives average PSNR of 54.25 and average MSE of 0.25 when hiding secret.image of_size “128*128” (131,072 bits) in different cover image of size 512*512.In spite of hiding the largest number of secret bits up to 546506 bits, which is approximately secret image of size 261 * 261 , the PSNR is still above 46 and the MSE is still less than 1.4 . This shows that the quality of the proposed technique in this paper is very good